THE USE OF WEB-SERVICES AND APPLICATIONS IN FORMING MEDIA LITERACY OF FUTURE JOURNALISTS - Тетяна Вікторівна Фісенко; Ольвія Олександрівна Гусак; Ольга Володимирівна Тріщук (Інформаційні технології і засоби навчання, 2021)
This research paper exposes functional features of the existing applications that are worth including in the journalism educational programs. Such inclusion will pursue the purpose of teaching media literacy to junior university students (namely, freshmen and sophomores) along with designing the Google browser AntiSepar Application. The application has been tested in practice by students majoring in journalism studies. The paper also sets the preconditions of the application’s technical tasks that were elaborated within the framework of the research project “Tools of asymmetric response to hybrid aggression in the humanitarian field” carried out at the Department of Publishing and Editing (Publishing and Printing Institute) at the National Technical University of Ukraine “Igor Sikorsky Kyiv Polytechnic Institute”, Kyiv, Ukraine. The designed questionnaire completed by university trainees has confirmed the efficacy of the developed system which can be a helpful tool for analyzing media content on a variety of topics (100 respondents filled out a survey).